‏ Examining the role of faith in overcoming human fear, sorrow and despair from the perspective of the Holy Quran - Rasa, Omid; Farahani, Mohammad (Researcher Bulletin of Medical Sciences, 2022)
Exploring and axplaining the role of faith in overcoming man's fear, sorrow, and despair in life from the perspective of the Holy Quran; in addition to the awareness and assistance of human societies in the treatment of human weakness and mental illness; It highlights the role and position of the Holy Quran in providing comprehensive solutions and unmatched answers to human questions and intellectual needs in life.This research has been done in the framework of analytical and descriptive methods and library method has been used to collect materials, and the concepts of the Holy Quran are the main reference and source for quoting its contents and arguments.In quoting the verses and concepts of the Holy Quran; the result was that man's faith and faithful behavior; it overcomes fear, sadness and frustration in life and Beneficial and valuable benefits such as: bring confidence, peace and satisfaction to human beings.God-centeredness and monotheism; trust and trust in God; cosmology and the hereafter; belief in reward and ultimately good; repentance and forgiveness; love and benevolence; among the causes and sources of the ability of believing human beings to overcome fear, sorrow and despair.